2008
DOI: 10.5465/amle.2008.31413859
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating Systemic Thinking in the Next Generation of Business Leaders

Abstract: In response to criticism that they do not train students to be effective decision makers, many business schools have attempted to modify their graduate management programs. We suggest that a primary ingredient missing from these attempts is a comprehensive treatment of systemic thinking. While most business functions teach about the systems housed within them, we suggest that few teach their students to think systemically. We propose a 3-part description of systemic thinking and provide results of a survey tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 18 publications
0
41
0
2
Order By: Relevance
“…While most students readily agreed that shortterm thinking was bad they still could not make key connections, between short term financial solutions and long term effects. This difficulty in connecting cause and effect when separated by time or space is well documented in systems dynamics literature (Forrester, 1971;Senge, 1990;Sterman, 2000;Atwater et al, 2008).…”
Section: Team Teaching Separate Classesmentioning
confidence: 99%
See 1 more Smart Citation
“…While most students readily agreed that shortterm thinking was bad they still could not make key connections, between short term financial solutions and long term effects. This difficulty in connecting cause and effect when separated by time or space is well documented in systems dynamics literature (Forrester, 1971;Senge, 1990;Sterman, 2000;Atwater et al, 2008).…”
Section: Team Teaching Separate Classesmentioning
confidence: 99%
“…Nevertheless, it is a necessary issue to address when trying to splice together two classes. The issue was discussed by Atwater et al (2008) when examining how to introduce system thinking into an MBA curriculum. A survey of several hundred professors, across a wide spectrum of disciplines, found that the majority felt systems thinking concepts were critical but should be taught in another area because there was no room for any new material in their classes.…”
Section: Introductionmentioning
confidence: 99%
“…Causality is explored as circular amplification loops, rather than just as a linear progression. Systems thinking is about overall effectiveness more than efficiency, about indirect, as well as direct consequences, about best value more than low cost, and explores alignment as a balancing act more than a problem-solving exercise (Atwater et al, 2008;Senge, 2006;Smith & Lewis, 2011).…”
mentioning
confidence: 99%
“…The ultimate objective of interdisciplinarity is systems thinking-an outcome in demand by businesses, but routinely neglected by business schools (Atwater et al, 2008). Systems thinking focuses on the big picture, instead of specific functional specializations and discrete organizational systems.…”
mentioning
confidence: 99%
“…Frequentemente, de forma involuntária, muitos erros são cometidos nas decisões de gestores (ATWATER; KANNAN;STEPHENS, 2008) que decorrem de vieses de pensamento "naturais" (KAHNEMAN;TVERSKY, 1977): problemas recorrentes são atribuídos a desempenhos individuais, sem perceber a estrutura que os condiciona; recursos são exauridos pela incapacidade de inferir a sua evolução ao longo do tempo; organizações e países envolvemse em escaladas irracionais que provocam grandes prejuízos, pela miopia que ignora a realimentação entre os elementos de um sistema e do ambiente sobre os sistemas abertos.…”
Section: Introductionunclassified